How Language Defines “Learning”: A Classroom View - Wynhoff Olsen, Allison (Acta Paedagogica Vilnensia, 2019)
[full article, abstract in English; abstract in Lithuanian] “Learning” is defined and constructed in classrooms as teachers and students interact through the use of language. As such, “learning” is situated language practices. Theories of socially- constructed uses of language and interactions provide foundation for this work. Through a microethnographic discourse analysis, the findings show a teacher and students constructing shared cultural models of “learning,” holding each other accountable to particular academic and pedagogical practices as well as uses of academic language. The teacher employed linguistic strategies to make visible and engage students in the academic language and “thinking” practices that counted as “learning.”